A Study of Ethnic Sports Situation and Development in Ethnic University Guangxi China - Ming, Li; Hengsuko, Ekasak; Promthep , Kreeta; Khantiyu, Yodkhwan (Journal of Roi Kaensarn Academi, 2024)
A study of ethnic sports situation and development in Ethnic University Guangxi China the objectives of this research were to study the situation and guidelines for the development of ethnic sports in ethnic university guangxi china using quantitative research methods. collected data from a sample were 10,000 people, using percentage criteria to determine the sample group. A sample size of 10 percent was used using simple random sampling, totaling 1200 people. The research instrument was a questionnaire on problems and guidelines for the development of ethnic sports. Data analysis used Average and percentage. The results of the study found that : 1. Ethnic students in Ethnic University Guangxi China have low attitudes towards ethnic sports percentage 49.58 2. Among the number of students who know about ethnic sports, 64.32% are mainly recommended by mobile phone 3. The current situation in which students are interested in and exercising in ethnic sports is to improve their health. Improved sports ability by 87.96 percent. 4. Development approach project promotion and school class activities and there is support and promotion.Official ethnic sports competitions within the university and outside the university with the government sector Various organizations are regularly involved. Conclusion: A study of ethnic sports situation and development in Ethnic University Guangxi China should guidelines for promoting ethnic sports activities in universities It is essential that there be clear and clear guidelines for promoting and preserving traditional culture. Raise awareness and access to ethnic sports Including creating understanding for students and staff. Develop public relations media to reach people of all ages. The university should play a role in supporting the budget for operations. Research related to supporting and promoting ethnic sports.